Increasing Collective Teacher Efficacy through Inuit Qaujimajatuqangit and Coaching: A Community-Based Approach - Mercer, Brenda (Scholarship@Western, 2019)
Abstract Instructional coaching in one remote northern community focuses on teacher mentorship and professional learning and prioritizes the implementation of prepackaged literacy resources. This focus on the implementation of prepackaged programs and data collection, promotes neo-liberal priorities and the privatization of education, over the methods that support the inclusion of Inuit cultural knowledge. Kostogriz (2011) states that we should be cautious about accepting the neo-liberal discourse of the literacy crisis and standardized reforms, the author suggests that low levels of literacy are not a large-scale problem so much as a result of under-provision of a socially just education. This Problem of Practice investigates the role of the learning coach in increasing collective teacher efficacy in accordance with the principals of Inuit Qaujimajatuqangit (IQ). Coaching to improve collective teacher efficacy through the integration of IQ may show greater educational improvement than literacy coaching alone. This vision for change includes an analysis coaching philosophy, leading from the middle, critical theory, organizational learning, the practice of decolonizing education and the positive effects of improving collective teacher efficacy. A PESTE analysis of the political, socio-economic factors; Bolman and Deal’s (2008) human resource frame and Nadler and Tushman’s (1980) congruence model will guide the critical organizational analysis. The leadership approaches to change are transformational, transformative and include ethical and decolonizing methods. The Change Path Model of Cawsey, Deszca, and Ingols (2016) is the chosen organizational framework for leading change in this Organizational Improvement Plan. Analysis of relevant internal data presents information on student educational attainment levels, and external data describes the positive effects of increasing collective efficacy on student achievement and school improvement. Hall and Hord’s (2006) six functions guide the coaching process and Change ...